(untitled) (Damascus University Journal of arts and humanities sciences, 2025)
Quranic discourse is an example of a specialized register that is implemented as a typical source of the Arabic language itself. One of the special aspects of the Quranic discourse is the contradiction between the apparent statement and the intended meaning, which is obvious in expressing the future using the past tense and expressing the past using the present or future reference. While this is a method that has long been used by Arabs as a technique to manifest eloquence, it poses some challenges for translators of the Quranic text into English. The aim of this study is to shed light on this rhetorical approach in Quran and to describe the translation strategies implemented by translators to deliver verb tense in English. The study is based on Ibn Qutaybah’s (1973) list of problematic issues in Quran. It emonstrates that, just with very few exceptions, in eneral, translators ignored this problematic contradiction between the apparent tense and the intended reference and attempted a translation based on meaning, where only the referred tense is used. This can be justified taking into consideration the structural differences between the two languages and the nature of the translated text. Some suggestions are provided when appropriate.